(untitled) (International Journal of Engineering and Computer Science, 2017)
In reversible data hiding, the data value are modified by some rules and the exact data can be re-stored after the extraction of data on the receiver system. Here optimal rule value under payload criteria is done by using iterative algorithm .it calculates the estimated embedded image-original image.the estimated image are modified according to the optimal value transfer. The images are divided in to the subsets. A receiver was successfully able to extract and recover the original content in the subsets on inverse order. Hence good payload distortion can be achieved